Expression of TRAIL receptors in human autoreactive and foreign antigen-specific T cells - Wendling, Uwe; Walczak, Henning; Krammer, Peter H. (Cell death and differentiation, 2000)
Deletion of T cells due to apoptosis induction is a regulatory mechanism in the human immune system that may be impaired in autoimmune diseases such as multiple sclerosis (MS). Involvement of the apoptosis-mediating CD95/CD95 ligand system in MS has been demonstrated. Here, we report that (auto)antigen-specific human T cells are not killed in vitro by soluble TNF-related apoptosis-inducing ligand (TRAIL) although expressing death-inducing receptors, TRAIL receptor 1 (TRAIL-R1) and TRAIL-R2. Apoptosis was assessed by caspase activation and DNA fragmentation, receptor expression was detected by RT-PCR and flow cytometry. The (auto)antigen-specific T cells were also resistant to specific TRAIL-R1/TRAIL-R2-directed induction of apoptosis, indicating that coexpression of the truncated TRAIL-R3 and TRAIL-R4 in these T cells is not responsible for the observed resistance. Upon stimulation, levels of death-inducing TRAIL receptors decreased whereas TRAIL was up-regulated on the cell surface. In contrast to CD95, the role of TRAIL receptors in MS might not involve regulation of T cell vulnerability.